1988
DOI: 10.1111/j.1469-8137.1988.tb04199.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and the responses of roots of maize (Zea mays L.) to physical impedance

Abstract: . SUMMARYThe response of the roots of maize seedlings to physical impedance was studied in glass chambers that enabled roots to be grown either unimpeded or in loosely packed small glass spheres (ballotini) and flushed with humidified air or other gas mixtures. Impedance decreased root length when measured after approxmiately 40 h by 30-60 "" and increased root diameter 10 cm behind the tip hy a similar percentage. Fresh weight was reduced by up to 28-40%, while ethylene evolution from roots was increased 2-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…3). Exogenous ethylene inhibits elongation and causes a similar pattern of swelling in maize primary roots at high water potential (Moss, Hall & Jackson 1988;Whalen & Feldman 1988). Second, it was shown that under water stress, ethylene production of ABA-deficient seedlings was substantially greater than in control plants (Figs 4 & 5), and this effect was completely prevented when the root ABA content was restored with exogenous ABA, together with restoration of root elongation .…”
Section: Aba Maintains Root Growth At Low Water Potentials By Restricmentioning
confidence: 92%
“…3). Exogenous ethylene inhibits elongation and causes a similar pattern of swelling in maize primary roots at high water potential (Moss, Hall & Jackson 1988;Whalen & Feldman 1988). Second, it was shown that under water stress, ethylene production of ABA-deficient seedlings was substantially greater than in control plants (Figs 4 & 5), and this effect was completely prevented when the root ABA content was restored with exogenous ABA, together with restoration of root elongation .…”
Section: Aba Maintains Root Growth At Low Water Potentials By Restricmentioning
confidence: 92%
“…Moss et al. (20) reported observations of ethylene production made 40 h after inhibitor treatment but did not record the status before the initiation of the impedance treatment or the shortterm responses. We applied inhibitors and monitored ethylene production even before pressure was applied.…”
Section: Discussionmentioning
confidence: 99%
“…However, the technique used to measure length (see "Materials and Methods") minimized the opportunity for overestimation; therefore, any potential error would shift all treatment curves in Fig. 3 (20) in which it was concluded that ethylene did not play an important role in tissue response to mechanical impedance. We believe the discrepancy between our results and this report may be explained by the differences in the way mechanical impedance was simulated in each case, the way inhibitors were applied, and the manner and timing of ethylene production measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations